Postoperative Nasal Septal Abscess Following Use of 2-Octylcyanoacrylate and Polydioxanone Plate in Open Septorhinoplasty: A Case Series. (October 2017) - Gall, Ryan; Bevans, Scott; Robitschek, Jon
Background: The employment of 2-octylcyanoacrylate adhesive (Dermabond) to assist graft placement in open septorhinoplasty has been increasingly used to stabilize cartilage grafts. Literature regarding this application has been mixed, with some showing the possibility of increased rates of inflammation, if not infection. We present an original comparative case series involving postoperative septal abscess formation adjacent to caudal strut grafting where both Dermabond and an absorbable polydioxanone (PDS) plate were used. Objective: To report an original comparative case series of patients who developed a postoperative septal abscess following open septorhinoplasty in the context of Dermabond application to affix cartilage to a PDS plate to facilitate caudal septal strut grafting. Design: Retrospective comparative series with relevant clinical photographs, culture studies, and surgical figures. Setting: Tertiary medical treatment facility. Results: Two patients underwent primary open septorhinoplasty with placement of an autologous caudal septal extension graft, which was stabilized using a PDS plate and secured into position using both Dermabond and PDS suture. Postoperatively, both patients presented a nasal septal abscess at an average of 8 weeks that required serial drainage and subsequent removal of the PDS plate in 1 of the patients. Cultures demonstrated mixed flora as well as Proteus mirabilis, previously unreported in the nasal septal abscess literature. In comparison to 8 patients who underwent reconstruction with PDS plate alone (without Dermabond application), this represents a relative risk of 15 ( P value = .053) for a septal abscess complication when Dermabond is employed . Conclusions: We present an original case series on our limited, though impactful experience with PDS plate reconstruction using Dermabond to facilitate caudal septal graft placement in open septorhinoplasty. In conjunction with previously reported case series, which demonstrated elevated risk of prolonged inflammation and infection, we would recommend avoidance of subcutaneous Dermabond as an adjunct, particularly in combination with PDS plate utilization.